Challenges During Review of COVID-19 Research Proposals: Experience of Faculty of Medicine, Ain Shams University Research Ethics Committee, Egypt - Marzouk, Diaa; Sharawy, Iman; Nakhla, Isabelle; El Hodhod, Mostafa; Gadallah, Hoda; El-Shalakany, Amr; Elwakil, Reda; Moussa, Mohammed M.; Ismail, Alaa; Tash, Fathy M. (Frontiers in Medicine, 2021)
The COVID-19 pandemic resulted in an overwhelming increase of research studies submitted to research ethics committees (RECs) raising a lot of ethical challenges. In the current article we aimed to report challenges encountered during reviewing of COVID-19 research and the experience of Faculty of Medicine, Ain Shams University, Research Ethics Committee (FMASU REC). Since April 10th, 2020 till October 13th the FMASU REC reviewed 98 COVID-19 research. This article tried to answer the question of how to face the overwhelming research submitted to the REC with practicing the ethical principles. Ethical challenges included new accelerated mode of review, online meetings, balance of risk versus benefit, measures to mitigate risks, co-enrolment in different studies, protection of vulnerable COVID-19 population, accelerated decisions, online research, how to handle an informed consent during the pandemic and justification of placebo arm.